(untitled) (Docentes 2.0 Journal, 2023)
Society constantly demands that students reach optimal levels of development of certain skills, one of the most common being the so-called digital skills. But to achieve this, teachers must have the skills to propose high-quality and innovative educational processes. Therefore, the present study aimed to determine the effect of digital competence on the professional development of teachers carried out under a process hypothetical deductive method, of the positivist paradigm, quantitative approach, non-experimental design, causal correlational, applied and cross-sectional type, where the population was made up of 40 teachers, and the sample was census type. Furthermore, to collect data, the survey was considered a technique, and two questionnaires were constructed, validated by experts, and with a reliability of 0.965 and 0.982, respectively. Regarding the results, with support in the ordinal logistic regression test, it was found that digital competence is an incident factor in professional development because the significance was valued at 0.000; in addition, this assertion was supported by the results Pseudo R2, which allowed us to conclude that the effect generated by digital competence explains 51.2% of the variability of professional development. According to Nagelkerke, 81.9% of professional development is caused by digital competence; in such a way, it was verified that participation in workshops or training programs Training in digital competence contributes to improving professional development and teaching practice.